Apparent digestibility of dry matter, protein and carbohydrate of the diet with biological corn meal silage in Cryphiops (C.) caementarius - Baltodano Tapia, Jean (2022)
The aim of this study was to determine the apparent digestibility of dry matter, protein and carbohydrates of the diet with biological corn meal silage in Cryphiops (C.) caementarius. Adult prawn (4.50 to 7.20 cm total length) was collected from the Pativilca river (Lima, Peru) and in the laboratory each shrimp was kept in individual containers set up in six aquaria (four prawn per aquarium). The experimental diet was supplemented with corn meal biological silage and the control diet was without silage; both diets had 1% chromic oxide. Each diet had three replicates. Prawn was fed twice a day (40% at 08:00 h and 60% at 18:00 h) at 6% of wet weight for 10 days. For feces collection, the prawn was transferred to a system of sieved boxes (12 compartments) installed inside an aquarium. Apparent digestibility was determined on a dry basis. Prawn fed the diet with corn meal biological silage had higher apparent digestibility coefficient for carbohydrates (95.69%), crude protein (80.02%) and dry matter (76.19%) than those fed the diet without silage (p<0.05), which was 93.48, 78.21 and 74.36%, respectively. The adult prawn digested efficiently the carbohydrates of the corn meal biological silage diet, instead of the protein of this diet.